Identifikasi Mikroorganisme Bakteri Laktobasilus sp dari Hasil Permentasi Ikan Channa Striata (Ikan Gabus) Bathin VIII Sarolangun Jambi - Muthiya Amalia; Ardi Mustakim (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This study aims to identify Lactobacillus sp. bacteria obtained from the fermentation of Channa striata fish (snakehead fish) originating from Bathin VIII, Sarolangun, Jambi. Snakehead fish is known to have high protein content and bioactive compounds that support the growth of probiotic microorganisms, especially lactic acid bacteria (LAB). Fermentation was carried out naturally for several days under controlled conditions, then isolation and characterization of bacteria were carried out through culture techniques on de Man Rogosa Sharpe Agar (MRSA) media. Initial identification was carried out using colony morphology tests, Gram staining, and basic biochemical tests. The isolation results showed the presence of round, convex, and milky white colonies, and showed Gram-positive and rod-shaped properties, which are typical characteristics of Lactobacillus sp. This study indicates that fermented snakehead fish can be a natural source of Lactobacillus sp. isolates that have the potential to be developed as probiotics in functional foods or local fermented products. These findings are expected to contribute to the development of local microorganism-based food technology and increase the economic value of snakehead fish in the Jambi region. Further research is needed to test the functional potential and safety of the isolated strains.